From detection to elimination: iron-based nanomaterials driving tumor imaging and advanced therapies - Xie, Dong; Sun, Linglin; Wu, Manxiang; Li, Qiang (Frontiers in Oncology, 2025)
Iron-based nanomaterials (INMs), due to their particular magnetic property, excellent biocompatibility, and functionality, have been developed into powerful tools in both tumor diagnosis and therapy. We give an overview here on how INMs such as iron oxide nanoparticles, element-doped nanocomposites, and iron-based organic frameworks (MOFs) display versatility for tumor imaging and therapy improvement. In terms of imaging, INMs improve the sensitivity and accuracy of techniques such as magnetic resonance imaging (MRI) and photoacoustic imaging (PAI) and support the development of multimodal imaging platforms. Regarding treatment, INMs play a key role in advanced strategies such as immunotherapy, magnetic hyperthermia, and synergistic combination therapy, which effectively overcome tumor-induced drug resistance and reduce systemic toxicity. The integration of INMs with artificial intelligence (AI) and radiomics further expands its capabilities for precise tumor identification, and treatment optimization, and amplifies treatment monitoring. INMs now link materials science with advanced computing and clinical innovations to enable next-generation cancer diagnostics and therapeutics.